Immersed in the Transitioning Higher Education Sector: The Impact of Transitions in the Higher Education Sector in England on Staff and Students - Tate, Adam; Glazzard, Jonathan (International Journal of Educational and Life Transitions, 2024)
The increasing marketisation of the UK higher education sector in recent years has resulted in multiple transitions for universities. Student evaluations of teaching and university league tables have placed greater importance on both the quality of teaching and student experience. Arguably, these have become regulatory mechanisms for holding lecturers and university managers to account. More recently, new metrics introduced by the Office for Students have resulted in continuation, completion and graduate employment rates being adopted as a proxy for the quality of teaching. These metrics regulate the sector and have resulted in changes to course availability, recruitment practices, course design, assessment practices and student placements. The UK higher education system operates within a discourse of performativity. The university experience, which was once a space for critical thinking and debate, has been transformed into preparing workers of the future who can enter the neoliberal market as oven-ready graduates who can make a contribution to the global economy. Universities have had to adapt to take their place within a neoliberal marketised society. However, these transitions have also resulted in transitions for university students who have been re-positioned as consumers and future workers. This paper draws on Multiple and Multi-dimensional transitions theory (Jindal-Snape, 2016) to explore the implications of these transitions.
Keywords: Transitions; Higher Education; Datafication; Neoliberal; Universities; National Student Survey